Obsesja przestrzeni? Niemieckie kształtowanie Europy Środkowej i Wschodniej - Rudawski, Bogumił (Studia Europaea Gnesnensia, 2015)
The main aim of the paper is to present the evolution of the German concept of space (Raum). The author focuses chiefly on the Nazi interpretations of space and the linking of geographical notion of space with racist ideology. This connection is demonstrated by means of a description of particular concepts of space, while relying on texts published in the press.